2020
DOI: 10.1002/hed.26191
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy guidelines developed at a large academic medical center during the COVID‐19 pandemic

Abstract: Background: During the SARS-CoV-2 pandemic, tracheostomy may be required for COVID-19 patients requiring long-term ventilation in addition to other conditions such as airway compromise from head and neck cancer. As an aerosol-generating procedure, tracheostomy increases the exposure of health care workers to COVID-19 infection. Performing surgical tracheostomy and tracheostomy care requires a strategy that mitigates these risks and maintains the quality of patient care.Methods: This study is a multidisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
2
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 17 publications
2
90
2
9
Order By: Relevance
“…Sixty (69.0%) patients had chronic medical illnesses, and the most common illnesses were hypertension (40.0%), coronary heart disease (21.1%), diabetes (17.5%) and cerebrovascular disease (10.0%) ( Table 1). Thirty (37.5%) patients received tracheostomies within 14 days after intubation, and their median duration between intubation and tracheostomy was signi cantly shorter than that of the late tracheostomy group ( [11][12][13][14][15][16][17][18][19][20][21], p = 0.034) at ICU admission and lower APACHE II scores (13 (SD 4) vs 17 (SD 6), p = 0.010) before tracheostomy. Among all 80 patients, lymphocytopenia and hypoalbuminemia at hospital admission and hypoxemia at ICU admission were prominent (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty (69.0%) patients had chronic medical illnesses, and the most common illnesses were hypertension (40.0%), coronary heart disease (21.1%), diabetes (17.5%) and cerebrovascular disease (10.0%) ( Table 1). Thirty (37.5%) patients received tracheostomies within 14 days after intubation, and their median duration between intubation and tracheostomy was signi cantly shorter than that of the late tracheostomy group ( [11][12][13][14][15][16][17][18][19][20][21], p = 0.034) at ICU admission and lower APACHE II scores (13 (SD 4) vs 17 (SD 6), p = 0.010) before tracheostomy. Among all 80 patients, lymphocytopenia and hypoalbuminemia at hospital admission and hypoxemia at ICU admission were prominent (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…During the pandemic of COVID-19, it remains unclear whether early tracheostomy performance is bene cial to critically ill COVID-19 patients. Some guidelines [16][17][18] suggested that tracheostomy should be delayed until at least 14 days from endotracheal intubation because viral load in the upper and lower airway may be high in the early course of the infection in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes the secretions are thick, so water based humidification is required but their use should be assessed on patient to patient basis. Nebulisers is helpful in secretion clearance by reducing the tenacity but require additional handling of ventilator circuits which can be avoided if possible and can waterlog HME filters; they should therefore be used only after careful consideration [29]. Above all patients inside ICU should be consulted in full PPE, facemask and shield.…”
Section: Post Tracheostomy Carementioning
confidence: 99%
“…Since initial reports suggest high viral load in the pharynx and respiratory secretions, there are important ramifications for optimal management of patients with head and neck cancer. This is especially true of patients with mucosal malignancies and those who require tracheotomy or laryngectomy 4‐6 . As is standard for management of head and neck cancers, multidisciplinary tumor board and conferences are critical for ensuring the safety of patients, caregivers, family members, health care providers, and the greater community 6‐8 .…”
mentioning
confidence: 99%